Stemphylium persianum sp. nov., (Pleosporales, Ascomycota) from Iran - Ahmadpour, Abdollah; Ghosta, Youbert; Alavi, Fatemeh; Alavi, Zahra; C. Karunarathna, Samantha; Tibpromma, Saowaluck (Phytotaxa, 2024)
Stemphylium species are saprophytes, or plant pathogens mostly associated with economically important crops. In this study, we isolated Stemphylium strains from grey to brown lesions on the culms of Schoenoplectus sp. (Cyperaceae, Poales). Based on combined morphological characteristics and sequence data of the internal transcribed spacer (ITS‒rDNA) region, parts of glyceraldehyde-3-phosphate dehydrogenase (gapdh) and calmodulin (cmdA) genes, the studied Stemphylium strains were identified and described herein as a new species, S. persianum. The new species is phylogenetically closely related to S. halophilum and S. lycii, however, they are distinguishable based on conidiophores, conidia, and ascospores morphology. Detailed morphological descriptions, illustrations, and phylogenetic relationships with other Stemphylium species are provided herein.